ChatGPT Adoption and Academic Achievement: The Full Mediation Role of Critical Thinking - Rita Budiyarti; Wisudani Rahmaningtyas (Research, Training and Philanthropy Institution Natural Aceh, 2026)
The rapid adoption of ChatGPT in higher education has transformed students' learning practices, yet its contribution to academic achievement remains inconclusive. This study investigates the direct and indirect effects of perceived usefulness, perceived ease of use, and digital literacy on academic achievement, with critical thinking serving as a mediating variable. A quantitative explanatory survey was conducted involving 214 students from the Office Administration Education Program at Universitas Negeri Semarang selected through proportionate stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital literacy directly improves academic achievement, whereas perceived usefulness and perceived ease of use show no significant direct effects. Critical thinking significantly predicts academic achievement and fully mediates the relationships between perceived usefulness and digital literacy with academic achievement, while no mediating effect is found for perceived ease of use. These findings extend the Technology Acceptance Model by highlighting critical thinking as the principal cognitive mechanism through which AI-supported learning enhances academic performance in higher education.